2023
DOI: 10.3390/dj11010023
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the Jaw

Abstract: Osteonecrosis of the jaw is a condition in which bone cells die due to various causes. It is classified as drug-induced jaw osteonecrosis, osteoradionecrosis, traumatic, non-traumatic, and spontaneous osteonecrosis. Antiresorptive or antiangiogenic drugs cause drug-induced osteonecrosis. The combination of medications, microbial contamination, and local trauma induces this condition. Osteoradionecrosis is a severe radiation therapy side effect that can affect people with head and neck cancer. It is described a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 97 publications
0
13
0
1
Order By: Relevance
“…Some studies have shown that there were even greater differences between the two jaws in terms of MRONJ localization: the lower jaw being affected in over 71% of patients compared to less than 22.5% in the upper jaw [61,67]. An explanation of the recorded differences could be due to less vascularity and a thinner mucosa in the mandible compared to the maxilla [68]. The most common location of the MRONJ area in the mandible would be the mandibular ramus, followed by the mandibular body and mandibular symphysis [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that there were even greater differences between the two jaws in terms of MRONJ localization: the lower jaw being affected in over 71% of patients compared to less than 22.5% in the upper jaw [61,67]. An explanation of the recorded differences could be due to less vascularity and a thinner mucosa in the mandible compared to the maxilla [68]. The most common location of the MRONJ area in the mandible would be the mandibular ramus, followed by the mandibular body and mandibular symphysis [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…A maintenance antiseptic program with non-alcoholic chlorhexidine 0.12% (two rinses per day, one week/month) is only indicated in people with MRONJ who are unable to undergo surgery due to comorbidities or non-deferrable antineoplastic therapies. The goal is to reduce the establishment of bacterial resistance and the deleterious repercussions of long-term chlorhexidine treatment [27,32].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to antiresorptive medications is primarily responsible for MRONJ. Other factors augment the effect of medications on pathogenesis (Table 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Review Etiology and Risk Factorsmentioning
confidence: 99%
“…Systemic diseases [16][17][18][19][20][21] Dental causes [21][22][23][24] Miscellaneous [21] Bisphosphonates The primary factor to consider while assessing the risk of developing MRONJ is the cumulative exposure of the patient to BP or denosumab, considering both the dose per treatment and the number of doses given from the start of the treatment [7][8][9][10][11][12][13][14][15]. There is no proven BP exposure cut-off below, which MRONJ has not been reported to date.…”
Section: Other Factorsmentioning
confidence: 99%